The influence of the chairman and CEO effectiveness on operating performance: Evidence from Malaysia - Sitraselvi Chandren; Sumaia Ayesh Qaderi; Belal Ali Abdulraheem Ghaleb (Cogent Business & Management, 2021)
This study investigates the relationship between the Chairman's characteristics (age, title, tenure, and ownership) and the firm's operating performance (measured by profitability and liquidity), and whether the Chief Executive Officer's (CEO) effectiveness (a combination of non-duality, age, and tenure) strengthens or impairs this relationship. Based on a total sample of 267 observations, we use Ordinary Least Squares (OLS) regression to investigate the hypotheses established for the top 89 non-financial firms listed on the Malaysian Main Market during 2017 to 2019. The findings show that Chairman age is positively and significantly associated with the firm's profitability but not with liquidity. Conversely, Chairman ownership is positively and significantly associated with liquidity but not with profitability. These findings suggest that the age and ownership of the Chairman may significantly boost operating performance. However, Chairman tenure is negatively and significantly associated with operating performance (profitability and liquidity), suggesting that long-tenured Chairmen are associated with poor operating performance. Chairman title is insignificantly related to operating performance. Importantly, the results also show that CEO effectiveness strengthens the relationship between Chairman tenure and liquidity. However, CEO effectiveness impairs the relationship between Chairman title and profitability and Chairman ownership and liquidity. Additional analysis is conducted to further check the validity of the main results and to avoid any possible effect of endogeneity issues. To our knowledge, this paper is the first to investigate the impact of Chairman characteristics on operating performance with the moderating effect of CEO effectiveness, specifically in a developing economy.
Keywords: 650; Chairman; CEO; corporate governance; operating performance; Malaysia